Delo z učenci s posebnimi potrebami - Resnik Planinc, Tatjana (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
In recent times characterised by rapid changes in knowledge, technology and also in values systems, children and adolescents with special educational needs have taken on a different place and role in the world compared to the past. Along with these changes, when it comes to people with special educational needs the ideas of integration, normalisation and, more recently, of inclusion have emerged and borne fruit. Through a qualitative pilot study we aimed to determine how geography teachers who teach in primary and secondary schools in Slovenia evaluate their own ability to work with students with special educational needs and garner their previous experience doing so. Geography teachers are aware of the importance of their tasks and accept them with full responsibility although they are critical about their own competencies. Among the main shortcomings of the current work in the inclusive school teachers mention an excessive number of pupils with special needs since the involvement of more than two pupils with different special needs can have a significant impact on their ability to achieve high quality teaching standards.
Keywords: geografija; geography; kvaliteta; mladostniki s posebnimi potrebami; osnovne šole; otroci s posebnimi potrebami; pouk; Slovenia; Slovenija; učitelji